Thirty day all-cause mortality in patients with Escherichia coli bacteraemia in England. (March 2015) - Abernethy, J.K.; Johnson, A.P.; Guy, R.; Hinton, N.; Sheridan, E.A.; Hope, R.J.
Abstract: Escherichia coli is the commonest cause of bacteraemia in England, with an incidence of 50.7 cases per 100 000 population in 2011. We undertook a large national study to estimate and identify risk factors for 30-day all-cause mortality in E. coli bacteraemia patients. Records for patients with E. coli bacteraemia reported to the English national mandatory surveillance system between 1 July 2011 and 30 June 2012 were linked to death registrations to determine 30-day all-cause mortality. A multivariable regression model was used to identify factors associated with 30-day all-cause mortality. There were 5220 deaths in 28 616 E. coli bacteraemia patients, a mortality rate of 18.2% (95% CI 17.8–18.7%). Three-quarters of deaths occurred within 14 days of specimen collection. Factors independently associated with increased mortality were: age < 1 year or > 44 years; an underlying respiratory or unknown infection focus; ciprofloxacin non-susceptibility; hospital-onset infection or not being admitted; and bacteraemia occurring in the winter. Female gender and a urogenital focus were associated with a reduction in mortality. This is the first national study of mortality among E. coli bacteraemia patients in England. Interventions to reduce mortality need to be multifaceted and include both primary and secondary healthcare providers. Greater awareness of the risk factors for and symptoms of E. coli bacteraemia may prompt earlier diagnosis and treatment. Changes in antimicrobial resistance patterns need to be monitored for their potential impact on infection and mortality.